2013
DOI: 10.22456/1982-8918.29087
|View full text |Cite
|
Sign up to set email alerts
|

A Baixa Representatividade De Mulheres Como Técnicas Esportivas No Brasil

Abstract: O estudo buscou identificar e analisar as razões associadas à baixa representatividade feminina no cargo de técnica. As informantes foram treze técnicas de oito modalidades. Os dados foram coletados através de entrevista semiestruturada e consultas com entidades esportivas. Constatou-se que as mulheres representam apenas 7% dos técnicos brasileiros. Como motivos para a pequena atuação feminina no cargo emergiram as barreiras enfrentadas pelas técnicas; a dificuldade de ascensão; a aceitação feminina da exclusã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
22

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 7 publications
0
4
0
22
Order By: Relevance
“…In addition, the authors found the lack of opportunities for the insertion and ascension of women, in sports leadership positions. As a last factor, it was found that the lack of recognition and low incomes faced by female coaches lead them to seek other jobs (Ferreira, Anjos, Drigo, Mourão, & Salles, 2018;Ferreira et al, 2013). As suggested by previous studies, the culture of sports reinforces the gender power structure of the society.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In addition, the authors found the lack of opportunities for the insertion and ascension of women, in sports leadership positions. As a last factor, it was found that the lack of recognition and low incomes faced by female coaches lead them to seek other jobs (Ferreira, Anjos, Drigo, Mourão, & Salles, 2018;Ferreira et al, 2013). As suggested by previous studies, the culture of sports reinforces the gender power structure of the society.…”
Section: Discussionmentioning
confidence: 87%
“…In the United States 57.4% of the head coaches in women's basketball are female (Walker & Bopp, 2010), which makes the Brazilian scenario an alarming context, regarding the opportunities to develop and qualify female coaches. On the other hand, previous studies showed that only 7% of the Brazilian head coaches in different sports are female (Ferreira et al, 2013), which makes the women's basketball context a less unequal workplace regarding gender issues. Similarly, Welch and Sigelman (2007) found in Division I Women's Sports that women coaches are more prevalent in basketball than in three other team sports.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…No Brasil essa particularidade não se restringe ao tênis. Segundo Ferreira et al (2013), apenas 7% dos treinadores em atividade no país são do sexo feminino.…”
Section: Discussionunclassified
“…Em estudo realizado por Ferreira et al (2013), destaca-se que apenas 7% dos técnicos esportivos brasileiros são mulheres em um total de 259 federações esportivas de 22 modalidades. Entre as federações pesquisadas, 71,4% não possuem mulheres cadastradas como técnicas, apontando uma desigualdade de oportunidades entre gêneros na atuação como treinadores.…”
Section: As Mulheres Nas Posições De Liderançaunclassified